Mating-type factor-specific regulation of the fumagillin/pseurotin secondary metabolite supercluster in Aspergillus fumigatus - Yu, Yidong; Blachowicz, Adriana; Will, Christine; Szewczyk, Edyta; Glenn, Steven; Gensberger-Reigl, Sabrina; Nowrousian, Minou; Wang, Clay C. C.; Krappmann, Sven (Molecular Microbiology, 2018)
In the human pathogenic mold Aspergillus fumigatus, sexual identity is determined by the mating-type idiomorphs MAT1-1 and MAT1-2 residing at the MAT locus. Upon crossing of compatible partners, a heterothallic mating is executed to eventually form cleistothecia that contain recombinant ascospores. Given that the MAT1 gene products are DNA binding master regulators that govern this complex developmental process, we monitored the MAT1-driven transcriptomes of A. fumigatus by conditional overexpression of either MAT1 gene followed by RNA-seq analyses. Numerous genes related to the process of mating were found to be under transcriptional control, such as pheromone production and recognition. Substantial differences between the MAT1-1- and MAT1-2-driven transcriptomes could be detected by functional categorization of differentially expressed genes. Moreover, a significant and distinct impact on expression of genetic clusters of secondary metabolism became apparent, which could be verified on the product level. Unexpectedly, specific cross-regulation of the fumagillin/pseurotin supercluster was evident, thereby uncoupling its co-regulatory characteristic. These insights imply a tight interconnection of sexual development accompanied by ascosporogenesis with secondary metabolite production of a pathogenic fungus and impose evolutionary constraints that link these two fundamental aspects of the fungal lifestyle.
EVALuna2:36418